The Role of YouTube as a Digital Da'wah Medium in Preventing Drug Abuse Among Teenagers - Wiwin Warliah Abdillah; Yahya Auliya Abdillah; Ahmad Mirzaq Miftahul Huda (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study examines the role of YouTube as a medium for digital da’wah in preventing drug abuse among adolescents. It aims to describe the dangers of drugs, identifies effective prevention strategies, and assesses the contribution of digital da’wah content to youth awareness. The research employs a descriptive qualitative approach based on literature review and content analysis of 12 YouTube videos consistently addressing anti-drug themes. Primary data were obtained from observations of video titles, view counts, durations, and audience interactions, while secondary data were drawn from journals, official BNN (National Narcotics Agency) reports, and relevant literature. The analysis reveals that anti-drug da’wah content combining religious and educational approaches is more effective in attracting adolescents’ attention and encouraging positive responses including intentions to avoid drugs rather than normative preaching. Three dominant strategies identified are persuasive and educational da’wah, collaborative da’wah (featuring interfaith and institutional dialogues such as with the BNN), and creative da’wah through interesting animations and visuals. However, its effectiveness is limited by competition with entertainment content, issues of credibility, and disparities in digital access and literacy. The study recommends strengthening cross-sector collaboration, improving content quality and validity, involving families and educational institutions in anti-drug campaigns, and innovating content formats to make them more appealing to adolescents. These findings support the use of YouTube as an integral part of a holistic strategy for drug abuse prevention.